A study of causes and effects of conflict in construction industry - Loke, Yi San (2013)
Nowadays, conflict seems like common and inevitable in the construction industry. Construction industry is a larger project which is complex since it involves variety of parties who are related to the project. Due to the multidisciplinary of the project participants, conflict becomes unavoidable issue in the construction industries. Internal conflicts that commonly involved the parties that directly participate in the project such as project developers, project consultants, and project contractors. Internal conflict can break the relationship among the participants, affect the work quality and productivity, and may lead to project fail if it is not manage in well. Thus, this research aim to identify the causes and effects that lead to internal conflict among three categories of the respondents, which are Developer, Contractor and Consultant. The survey questionnaire had been used in collecting the data from 134 of the respondents. The literature review in this study highlighted 4 main causes such as Contractual problems, Design/scope related problems, Management problems and Behavioural problems; and 4 main effects which are Time, Cost, Productivity and Quality, and Organization and its reputation related effects. Based on the analysis result from the collected data, the 4 most significant causes are Error and Omission in Project Design, Ambiguities in Contract Documents, Error and Omissions in the Contract Terms and Improper Planning and Scheduling, whereas most significant effects of internal conflict are Delay in Project Duration, Lost of Profitability, and Project Cost Overruns. Besides this, the Pearson Correlation Coefficient Analysis and Spearman Rank Correlation Analysis had been used to test the strength of relationship between causes and effects of internal conflict, and test the degree of agreement between 3 categories of respondents to the causes and effects. In overall, the correlation between causes and effects shown moderate positive in relationship, and there is no same agreement among that 3 categories of respondents.